Produção e qualidade fisiológica de sementes de feijão mungo em função de densidade populacional de plantas - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The reasons for the low yield in mung bean production are many, and usually related to inadequate management, varieties, and agronomic management. Considering the challenges faced by the legume producers, we need to invest in alternative ways to maximize the yield per area unit, by applying appropriate technologies and management practices to the cultivation of the species, with sowing rate being an important component. In this sense, the objective of this study was to obtain data to allow the indication of the most suitable plant populations for the cultivation of the mung bean, in terms of commercial yield and physiological quality of freshly harvested and stored seeds. To this end, the experiment was conducted in the field at the State University of Goiás - Ipameri Campus, in which mung bean production was evaluated considering row spacing and the number of plants per linear meter from December 2017 to March 2018. The experimental design was the one with randomized blocks with treatments arranged in subdivided plots, having in the plots two spacings between rows (25 and 50 cm) and in the subplots six numbers of plants per linear meter (4, 8, 12, 16, 20 and 24 plants) with four replicates. The experimental units had the following dimensions: 4.0 m long and 2.5 m wide, with a useful area of 4m2. The 50-cm spacing was composed of four rows, the two central ones being considered as the useful area and the two lateral ones as the borders. The 25-cm spacing was composed of eight lines, the four central ones were considered as the useful area, the two lateral ones on the left and two on the right side as the borders. In the useful plot, plant height, stem diameter, number of pods per plot, pod length, pod width, number of grains per pod, the mass of one hundred pods, the one hundred grain mass, and its productivity were evaluated. The largest 100-seed mass was reached in the 50cm-spacing between rows. The 50cm-spacing between rows and 24 plants per linear meter increases the yield of Mung bean. After the completion of the field experiment, the physiological quality of the seeds was evaluated. To evaluate the physiological quality of mung bean seeds, tests were carried out to determine the degree of moisture, germination, and seed vigor at the Multidisciplinary Laboratory II of the State University of Goiás – Ipameri Campus, from February to August 2018. The experimental design used for both experiments was completely randomized, with the treatments arranged in a 2 x 6 factorial scheme, taking as factors the spacings between rows (25 and 50 cm) and numbers of plants per linear meter (4, 8, 12, 16, 20 and 24 plants), and with four replicates. The tests were performed with freshly harvested seeds and stored seeds. The newly harvested seeds produced in the 50 cm spacing between rows and with 24 plants per linear meter a showed better physiological potential, evidenced by seedling length, seedling root length, electric conductivity and the mass of one thousand seeds. As for the stored seeds, the 50 cm spacing between rows and with 24 plants per linear meter between rows, a presented better physiological potential, evidenced by the mass of a thousand seeds and electrical conductivity. Seeds produced in 50 cm spacing between rows and with 24 plants per linear meter, present a better physiological potential for both freshly harvested seeds and seeds stored for a six-month period.
Keywords: Vigna radiata; Arranjo de plantas; Potencial fisiológico; Vigna radiata; Arrangement of plants; Physiological potential; CIENCIAS AGRARIAS